Biomimetic Catalytic Decarboxylation of Phenylacetic Acid Derivatives by Manganese(III) Complex - Montazerozohori, M.; Nasr-Esfahani, M.; Joohari, S.; Akhlaghi, P.; Dehghani, A. (Asian Journal of Chemistry, 2010)
Bis(2-hydroxyacetophenone)ethylendiimine as a quadridentate Schiff base ligand and its Mn(III) were synthesized and characterized by analytical and spectral data. An efficient homogeneous oxidative decarboxylation of some carboxylic acids was performed by catalytic amount of Mn(III) complex in chloroform, using tetrabutylamonium periodate as oxidant at room temperature.